ANALYTICAL QUALITY BY DESIGN APPROACH FOR DEVELOPMENT OF UV SPECTROPHOTOMETRIC METHODS IN THE ESTIMATION OF TROSPIUM CHLORIDE FROM CAPSULE DOSAGE FORM - Jadhav, Monika L.; Tambe, Santosh R.; Girase, Manoj V. (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The aim of present work is to develop and validate two spectrophotometric methods for trospium chloride estimation in capsule dosage form using Analytical Quality by Design (QbD) approach as per ICH Q8 (R2) guidelines. Methods: Variable parameters like type of sample preparation, solvent, wavelength, instrumental parameters such as slit width, scan speed and sampling interval etc. were designed into Ishikawa diagram and critical parameters were determined by observation as well as by using principal component analysis. Results: In simple spectrophotometric method, trospium chloride was estimated at 258 nm using 0.1 N sodium hydroxide. Beer's law was obeyed in the concentration range 200-1000 Î¼g/ml (r2 = 0.999). In first derivative spectrophotometric method, beer's law was obeyed in concentration range 20-100 Î¼g/ml (r2 = 0.999) at 226.6 nm using 0.1 N sodium hydroxide. The proposed methods were validated according to ICH Q2 (R1) analytical method validation guidelines. Conclusion: The proposed methods were found to be accurate, precise, and economical and can be applicable for routine quality control analysis of trospium chloride on pharmaceutical dosage form. Implementation of QbD approach resulted in more robust methods which can produce consistent, reliable, and quality data throughout the process and also save time and money.